The Differences of Oral Mucosa Disease between Undernutrition and Stunting Toddlers in Jember - Inaayatul Maula; Sofira Nadia; Ristya Widi Endah Yani; Dyah Indartin Setyowati (Health Notions, 2022)
Inadequate nutritional intake when the fetus is born until the early baby is born affects the growth and development of toddlers, which has an impact on malnutrition and stunting. This research aims to analyse the differences of oral mucosa at undernutrition and stunting toddlers in Jember. The study was conducted in Jelbuk District, Jember. A cross-sectional study was applied in this research. The research population was undernutrition toddlers in Silo and Jelbuk with purposive sampling technique. The variables in this research were undernutrition, stunting, and soft tissue diseases of the oral cavity (angular cheilitis, glossitis, cheilitis, recurrent aphthous stomatitis). The samples were 40 undernutrition toddlers and 40 stunting toddlers. The inclusion criteria of respondents were the undernutrition and stunting toddlers aged 24-60 months. While the exclusion criteria were physical disability and mental disorder toddlers. The statistic data of this research were analysed using a Mann–Whitney U Test. The male experienced more undernutrition and stunting based on the gender. The highest percentage of glossitis in undernutrition under five was about 47.5%. The highest percentage of angular cheilitis in stunted toddlers was about 42.5%. The Mann–Whitney U test  statistical test resulted in a significance of 0.439. In conclusion, there is no difference on oral mucosa disease between undernutrition and stunting toddlers. Keywords: oral mucosa; undernutrition; stunting